2019
DOI: 10.1186/s13019-019-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of radical pericardiectomy for constrictive pericarditis in Korean population

Abstract: BackgroundThe extent of pericardiectomy is an important issue in constrictive pericarditis but its impact on long-term outcomes has been rarely reported. We compared long-term results of radical pericardiectomy with conventional phrenic to phrenic pericardiectomy.MethodsNinety patients who underwent pericardiectomies between February 1995 and April 2015 were reviewed retrospectively. They were classified into conventional (n = 37) and radical (n = 53) groups according to pericardiectomy being performed anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
(39 reference statements)
1
24
0
1
Order By: Relevance
“…Surgical pericardiectomy can restore the normal physiology, provided that there is no cardiomyopathic component. It has been shown that radical pericardiectomy is superior to conventional in terms of long-term mortality, right ventricular systolic pressure and tricuspidal regurgitation (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical pericardiectomy can restore the normal physiology, provided that there is no cardiomyopathic component. It has been shown that radical pericardiectomy is superior to conventional in terms of long-term mortality, right ventricular systolic pressure and tricuspidal regurgitation (5) .…”
Section: Discussionmentioning
confidence: 99%
“…The surgical methods are classified as complete pericardiectomy and partial pericardiectomy according to the extent of pericardial resection. Complete pericardiectomy has been proven to be not only associated with lower perioperative mortality [9] but also confer significant long-term survival benefit and clinical functional improvement [10,18]. Generally, pericardiectomy can be performed through either median sternotomy or left anterolateral thoracotomy, while median sternotomy provides adequate exposure of the right atrium, right ventricle and the vena cava, thus enabling extensive pericardial resection [19].…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, the extent of pericardiectomy is varied according to surgeons' experience and surgical difficulty. However, complete pericardiectomy has been reported to be superior to partial pericardiectomy in the improvement of hemodynamics and prognosis [9,10], while the factors influencing the outcomes after pericardiectomy still remain unclear, especially in tuberculous constrictive pericarditis. This study aimed to identify the determinants of postoperative complication and prolonged intensive care unit (ICU) stay after pericardiectomy in tuberculous constrictive pericarditis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the incidence of postoperative complication and death, some studies have attempted to nd the possible risk factors to improve the strategies of perioperative management. The extent of pericardial resection was one of the risk factors and complete pericardiectomy was associated with superior surgical outcomes to partial pericardiectomy [16,23,24] . Cardiopulmonary bypass was also a predictor of poor prognosis and the 30-day mortality rate might reduce without the use of cardiopulmonary bypass [25] .…”
Section: Discussionmentioning
confidence: 99%